PARTISIPASI ORGANISASI MASYARAKAT PEDULI API (MPA) TERHADAP PENCEGAHAN DAN PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN PELALAWAN - Tengku Evayanti; Zulkarnaini Zulkarnaini (Jurnal Ilmu Lingkungan, 2014)
The purpose of this research is to analyze the relationship between consciousness,rules, organization, income, skills and means of participation of civil societyorganizations concerned with fire either partially or simultaneously and thenanalyze the relationship between the participation of civil society organizationsconcerned with fire prevention and control of forest fire in Pelalawan. The methodused was a survey method. Sources of data in this study were people who joined inthe concern groups contained fire in Pelalawan numbered 320 people in 16 groupsand set up as many as 175 samples (55%) by using proportional random samplingmethod. Techniques of data analysis using ordinal data with Spearman rankcorrelation formula. Based on the survey results revealed that there is a positive andsignificant factor awareness, rules, organization, income, skills and means ofparticipation of civil society organizations concerned with fire in Pelalawan, notethat the factor of skill / expertise is the biggest factor has a relationship with theparticipation of civil society organizations care fire that is 0.730 when comparedwith other factors; later also proved that there is a positive and significantrelationship awareness, rules, organization, income, skills and facilities togetherwith the participation of civil society organizations concerned fire in Pelalawan, themagnitude of the relationship for 0741. Proved that there is a positive relationshipand significant participation of civil society organizations concerned with fireprevention and control of forest fire in Pelalawan with Spearman rank correlationvalue of 0.800.